Organization characteristics: Can they influence the construction innovation? - Ng, Weng Seng (UUMPRESS and Managed by STML, 2020)
Heavy constructions are increasingly becoming more complicated, demanding increased innovative methods, and greater technological advancement. The complexity of the industry, generally has been described as multi-faceted and highly fragmented with significant problems such as communication breakdown, conflicts, and disputes. The lack of organization characteristics can apparently limit the effort of the construction industries to adopt the technology and innovation. Hence, this paper aims to investigate to the influence of organization characteristics namely construction type, presence of trade unions, and professional and trade association affiliation towards the construction innovation. In order to achieve the research objectives, mail surveys have been conducted among the construction companies in Malaysia. A total of 703 questionnaire surveys were mailed to randomly selected construction companies that operating in Malaysia and registered as G7 contractor with CIDB. The number of returned usable surveys totaled 383, yielding an effective response rate of 54.4%. All the organizational characteristics proposed have been found to be positively correlated with construction innovation.Apart from suggesting the direction of future construction industry study, this paper is valuable in providing insights for the contractors in implementing innovative construction technologies that can be used to devise strategic marketing plans and ultimately for enjoyment of competitive advantages.